Role of Macrophage Migration Inhibitory Factor in Granulomatosis With Polyangiitis. Issue 12 (22nd October 2018) - Sreih, Antoine G.; Ezzedine, Rana; Leng, Lin; Fan, Juan; Yao, Jie; Reid, Duncan; Piecychna, Marta; Carette, Simon; Cuthbertson, David; Dellaripa, Paul; Hoffman, Gary S.; Khalidi, Nader A.; et al.
Abstract : Objective: To examine the association between macrophage migration inhibitory factor (MIF) promoter polymorphisms and granulomatosis with polyangiitis (GPA) in human subjects, and to assess the role of MIF in a murine model of granulomatous vasculitis. Methods: The human study involved 1, 077 patients with GPA and healthy controls whose serum was genotyped by capillary electrophoresis for the MIF −794 CATT5−8 promoter microsatellite ( rs5844572 ). MIF promoter, CATT‐length–dependent gene expression in response to β‐glucan was assessed by gene reporter assays. In mouse studies, granulomatous disease was induced by injection of Candida albicans β‐glucan into wild‐type (WT) or Mif ‐knockout ( Mif ‐KO) C57BL/6 mice and C57BL/6 mice transgenically overexpressing Mif in lung epithelium ( Mif lung–Tg2.1). Mice were treated with a neutralizing anti‐MIF antibody and analyzed for the density of pulmonary granulomas, expression of inflammatory chemokines, and frequency of mortality. Results: The percentage of human subjects carrying >5 CATT repeats in each MIF allele (high genotypic MIF expressers) was 60.2% among patients with GPA and 53.9% among healthy controls (adjusted P = 0.049). In response to granulomatous stimulation, human MIF gene expression increased proportionally with CATT length. Mif lung–Tg2.1 mice exhibited more pulmonary granulomas than WT mice, which in turn showed more granulomas than Mif ‐KO mice. A significantly higher percentage of Mif lung–Tg2.1 mice, compared to Mif‐ KO or WT mice, died when injected with Candida albicans β‐glucan, and treatment of these mice with an anti‐MIF monoclonal antibody protected against a lethal outcome. Levels of MIF‐dependent neutrophil/macrophage chemokines were elevated in the bronchoalveolar lavage fluid or plasma of Mif lung–Tg2.1 mice. Conclusion: Patients with GPA have an increased frequency of high MIF expression CATT alleles. Higher Mif expression increases the incidence of mortality and pulmonary granulomas in Mif lung–Tg2.1 mice, while anti‐MIF treatment protects these mice against death. Blockade of MIF in high genotypic MIF expressers may therefore offer a selective pharmacologic therapy for GPA.